The struggles and the triumphs of South African Black women professors - Zulu, N. T. (South African Journal of Higher Education, 2020)
The apartheid epoch introduced a web of laws that influenced public and private structures and ideological apparatuses, including educational institutions, to give an inferior status to Black people. South Africa was also upheld by a deeply patriarchal system which marginalised the status of women in society. This meant that most people in senior positions in South African organisations were predominantly white and male. The consequence of racism and patriarchy meant that there have been a low number of Black women professors in institutions of higher education. This study therefore aimed to examine the discourses of Black women professors in post-apartheid South Africa. This study used the Critical Race Theory (CRT) and critical consciousness, to understand the challenges that Black women professors encounter and how they strategically navigated these challenges in institutions of higher education, respectively. The Black women professors were recruited from two South African universities. Semi-structured interviews were used to collect the data. The data was analysed using thematic analysis. The significance of the study is that it identified discourses, which could be useful to understand the kinds of challenges that may operate in higher education and ways to shift these existing challenges. The findings showed two main challenges encountered by Black women professors namely: (1) feelings of being unwelcomed within the academic space and (2) being undermined in their leadership positions. Black women professors seemed to navigate these challenges by (1) being vocal, and (2) being intentional, about excelling in their work and (3) adopting a transformational leadership style. The study feeds into how South African higher education institutions can accommodate Black women professors, as they navigate through their career.